The expirience of IDEAL - E. Z. Burnevich (Журнал инфектологии, 2014)
Combination therapy with pegylated interferon-α and ribavirin is the modern standard of chronic hepatitis C treatment [1-3] in Russian Federation [4]. This particular regimen provides achieving of sustained virological response (SVR) in 42-28% of patient with genotype 1 chronic hepatitis C [5,6]. IDEAL (Individualized Dosing Efficacy vs. flat dosing to Assess optimaL pegylated interferon therapy) study was designed to assess the most optimal and effective antiviral therapy regiment. IDEAL was randomized, in parallel groups, multicenter phase IIIb study to assess efficacy and safety of two combination regiment with pegylated interferon alfa-2b (dosing regimens: 1,5 and 1,0 mcg/kg/week) and ribavirin, administered according to body weight (800–1400 mg/day) compared with pegylated interferon alfa-2a 180 mcg/week in combination with ribavirin 1000–1200 mg/day in genotype 1 chronic hepatitis C patients.